Hybrid de novo genome assembly data and comparative genomics of Fusarium chlamydosporum isolated from infected blackberry fieldsNCBINCBI/SRAZenodoNCBI - Anton Pashkov; José Pedro Martínez-Hernández; Alfredo Herrera-Estrella; Pablo Cruz-Morales; Nelly Selem-Mojica; José Manuel Villalobos-Escobedo (Data in Brief, 2025)
Here, we present a dataset of ITS and β-tubulin sequences, along with a phylogenetic analysis using these molecular markers, for six putative Fusarium strains isolated from blackberry field soil. Additionally, we report the sequencing and hybrid assembly of one of these strains, identified as Fusarium chlamydosporum. Whole-genome sequencing of this strain was conducted using Illumina NovaSeq 6000 and Oxford Nanopore MinION technologies, resulting in a high-quality hybrid assembly of approximately 37 Mb across 23 contigs, with over 99 % completeness. Phylogenomic analysis, incorporating 88 Fusarium genomes, confidently placed this strain within the F. chlamydosporum clade. This assembly is now the NCBI reference genome for F. chlamydosporum, providing a valuable resource for future genomic and evolutionary studies of this species.